The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1186/1471-2407-14-772
|View full text |Cite
|
Sign up to set email alerts
|

Prognostication of patients with clear cell renal cell carcinomas based on quantification of DNA methylation levels of CpG island methylator phenotype marker genes

Abstract: BackgroundThe CpG island methylator phenotype (CIMP) of clear cell renal cell carcinomas (ccRCCs) is characterized by accumulation of DNA methylation at CpG islands and poorer patient outcome. The aim of this study was to establish criteria for prognostication of patients with ccRCCs using the ccRCC-specific CIMP marker genes.MethodsDNA methylation levels at 299 CpG sites in the 14 CIMP marker genes were evaluated quantitatively in tissue specimens of 88 CIMP-negative and 14 CIMP-positive ccRCCs in a learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 25 publications
2
41
0
Order By: Relevance
“…The peaks obtained for the synthetic DNA fragments 5, 6, 7 and 8, which contained 20 gene for discrimination of more aggressive CIMP-positive ccRCC from CIMP-negative ccRCC in our previous study using specimens of tumorous tissue and MassARRAY analysis. 16 After 10 measurements were taken for each fragment, excellent concordance of the retention time for each fragment was revealed ( Figure 2D), indicating the reproducibility of HPLC analysis using the newly developed column. In addition, it was revealed that a difference in methylation level of 5% (ie, 20% vs 25% [P = 4.77 9 10 À11 ] and 25% vs 30% [P = 1.16 9 10 À8 ]) would be statistically distinguishable ( Figure 2D) in a clinically feasible setting.…”
Section: Determination Of Quantitativeness Andmentioning
confidence: 65%
See 4 more Smart Citations
“…The peaks obtained for the synthetic DNA fragments 5, 6, 7 and 8, which contained 20 gene for discrimination of more aggressive CIMP-positive ccRCC from CIMP-negative ccRCC in our previous study using specimens of tumorous tissue and MassARRAY analysis. 16 After 10 measurements were taken for each fragment, excellent concordance of the retention time for each fragment was revealed ( Figure 2D), indicating the reproducibility of HPLC analysis using the newly developed column. In addition, it was revealed that a difference in methylation level of 5% (ie, 20% vs 25% [P = 4.77 9 10 À11 ] and 25% vs 30% [P = 1.16 9 10 À8 ]) would be statistically distinguishable ( Figure 2D) in a clinically feasible setting.…”
Section: Determination Of Quantitativeness Andmentioning
confidence: 65%
“…In our previous study, 14 ccRCC included in the present study were found to be CIMP-positive using genome-wide DNA methylation analysis by Infinium assay 11 and DNA methylation quantification of the 7 ccRCC-specific CIMP marker genes using the MassARRAY system. 16 Although the present stratification of 16…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations